Peningkatan Kompetensi Digital Guru SMK Melalui In House Training - Arifuddin, Arifuddin (Journal of Community Service and Society Empowerment, 2023)
The aim of this community service activity is so that teachers at SMK Negeri 2 Parepare City have understanding and competence regarding the implementation of the independent curriculum. One of the materials is Increasing Digital Competence Through In House Training. The method used is coordination and synchronization with partners, namely the teachers of Negeri 2 Parepare, training and mentoring on the Digital Electronic Archives System system. The results obtained are 1) Increased information and insight among vocational school teachers, 2) Vocational school teachers also have skills in using digital-based filing system software, 3) More than 80% of vocational school teachers have excellent digital-based filing system skills. ..